1983
DOI: 10.2307/203716
|View full text |Cite
|
Sign up to set email alerts
|

Secular Changes in American and British Stature and Nutrition

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. . The MIT Press and the Massachusetts Institute of Technology and the editors of The Journal of Interdisciplinary History are collaborating with JSTOR to digitize, preserve and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(37 citation statements)
references
References 0 publications
0
36
0
1
Order By: Relevance
“…Fogel et al (1983) found an average height beginning with the American Revolution until World War II of approximately 68.0 in. (172.7 cm), whereas we document mean heights of 70.4–72.1 in.…”
Section: Discussionmentioning
confidence: 99%
“…Fogel et al (1983) found an average height beginning with the American Revolution until World War II of approximately 68.0 in. (172.7 cm), whereas we document mean heights of 70.4–72.1 in.…”
Section: Discussionmentioning
confidence: 99%
“…During the Civil War, approximately 95 percent of white males between age 18 and 25 in the United States were examined and approximately 75 percent of the examinees were inducted (Fogel, Engerman, and Floud 1983). Comparisons between the Union Army sample and the northern population in the same age group suggest these two groups resemble each other in terms of wealth in 1850 and 1860 and in terms of mortality circa 1900 (Fogel et al 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Elo and Preston 1992; Davey-Smith, Gunnell, and Ben-Shlomo 2001; Blackwell, Hayward, and Crimmins 2001; Hayward and Gorman 2004; Luo and Waite 2005). Height, as a proxy of net intake of nutrition during growing years (Fogel, Engerman, and Floud 1983; Fogel 1993; Riley 1994), was also found to be related to adulthood mortality (e.g. Waaler 1984; Costa 1993; Fogel and Costa 1997; Fogel 2004).…”
Section: Introductionmentioning
confidence: 96%
“…11,38 While genetic characteristics explain about 80% of stature variation within most populations, it is clear that nutrition, energy expenditure and disease exposure during childhood influence the ability of individuals to realise their height potential. A considerable body of literature now shows that environmental and socio-economic conditions rather than genetics explain most of the variation in height across societies, or even groups within a society.…”
Section: Sources Of Height Evidencementioning
confidence: 99%
“…A considerable body of literature now shows that environmental and socio-economic conditions rather than genetics explain most of the variation in height across societies, or even groups within a society. 10,[38][39][40] Heights have also been used to study living standards in other African countries, like Kenya, Ghana and Côte d'Ivoire. [40][41][42] In a recent analysis of individuals born between 1951 and 1992 in 39 developing countries, Akachi and Canning 43 found that a 1-cm gain in cohort height was associated with a 6% increase in income per capita and a 1.25-year increase in life expectancy.…”
Section: Sources Of Height Evidencementioning
confidence: 99%